"Chronic sensory demyelinating neuropathy": chronic inflammatory demyelinating polyneuropathy presenting as a pure sensory neuropathy. Issue 8 (August 1992) - Oh, S J; Joy, J L; Kuruoglu, R
Abstract : The clinical electrophysiological and histological features of 10 cases of "chronic sensory demyelinating neuropathy" (CSDN) are reported. This entity is characterised by: 1) subacute or chronic progression; 2) pure sensory neuropathy; 3) high spinal fluid protein in the majority of cases; 4) electrophysiological evidence of demyelination affecting motor as well as sensory nerve fibres; 5) demyelination on sural nerve biopsy and 6) good response to immunotherapy in progressive phase. It is believed that this entity represents chronic inflammatory demyelinating polyneuropathy (CIDP) presenting as pure sensory neuropathy.